Immunotherapy: A Potential Approach for High-Grade Spinal Cord Astrocytomas - Hu, Jie; Liu, Tie; Han, Bo; Tan, Shishan; Guo, Hua; Xin, Yu (Frontiers in Immunology, 2021)
Spinal cord astrocytomas (SCAs) account for 6–8% of all primary spinal cord tumors. For high-grade SCAs, the prognosis is often poor with conventional therapy, thus the urgent need for novel treatments to improve patient survival. Immunotherapy is a promising therapeutic strategy and has been used to treat cancer in recent years. Several clinical trials have evaluated immunotherapy for intracranial gliomas, providing evidence for immunotherapy-mediated ability to inhibit tumor growth. Given the unique microenvironment and molecular biology of the spinal cord, this review will offer new perspectives on moving towards the application of successful immunotherapy for SCAs based on the latest studies and literature. Furthermore, we will discuss the challenges associated with immunotherapy in SCAs, propose prospects for future research, and provide a periodic summary of the current state of immunotherapy for SCAs immunotherapy.